A combined solution for flexible control of poultry houses. (12th March 2022) - Schmidt, Lucas; Casanova, Dalcimar; Ribeiro, Richardson; Teixeira, Marcelo; Gomes, Heitor M.
In poultry houses, thermal comfort is decisive for maximising the feed conversion rate, a measure for successful production. As there are different automatic control options, that result in variable performance indexes, this paper reproduces, tests, and compares two of them: a reactive, that applies event-driven methods, and a bio-inspired, which is based on artificial intelligence techniques. As each approach adds specific advantages to the process control, we combine them into a single framework that gathers their best features. Simulations using real data show that temperature and humidity have been reproduced with 97% and 80% precision, respectively. In comparison, reactive and bio-inspired approaches show respectively accuracies of 90% and 82% for temperature, and 60% and 66% for humidity. Therefore, we conclude that our approach can improve both reactive and bio-inspired control, standing as a feasible and flexible alternative for the control of poultry houses.